Animal legacies lost and found in river ecosystems. (1st November 2021) - Frauendorf, Therese C; Subalusky, Amanda L; Dutton, Christopher L; Hamilton, Stephen K; Masese, Frank O; Rosi, Emma J; Singer, Gabriel A; Post, David M
Abstract: Animals can impact freshwater ecosystem structure and function in ways that persist well beyond the animal's active presence. These legacy effects can last for months, even decades, and often increase spatial and temporal heterogeneity within a system. Herein, we review examples of structural, biogeochemical, and trophic legacies from animals in stream and river ecosystems with a focus on large vertebrates. We examine how the decline or disappearance of many native animal populations has led to the loss of their legacy effects. We also demonstrate how anthropogenically altered animal populations, such as livestock and invasive species, provide new legacy effects that may partially replace lost animal legacies. However, these new effects often have important functional differences, including stronger, more widespread and homogenizing effects. Understanding the influence of animal legacy effects is particularly important as native animal populations continue to decline and disappear from many ecosystems, because they illustrate the long-term and often unanticipated consequences of biodiversity loss. We encourage the conservation and restoration of native species to ensure that both animal populations and their legacy effects continue to support the structure and function of river ecosystems.